The Role of Long-Chain Polyunsaturated Fatty Acids in the Nutrition of Infants - D.O. Dobrianskyi (Zaslavsky O.Yu., 2015)
Long-chain polyunsaturated fatty acids (LCPSFA) are the main functional fats of mother's milk. The predominant and functionally most important LCPSFA are arachidonic acid (AA) and docosahexanoic acid (DHA). In addition to imitation of breast milk, there are two important reasons to add LCPSFA in infant formula for babies. Firstly, infants can not synthesize sufficient number of LCPSFA to compensate for the lack of these substances in food. Secondly, the brain tissue, the retina of the eyes and immune system require a large number of LCPSFA as a building material and functional components to support intensive growth and development in early childhood. This period is critical for the formation and development of organs, therefore, optimal supply of substrates is necessary for their optimal functioning. These ideas, combined with the results of over 20 randomized controlled clinical trials and numerous other studies that show the positive impact of food LCPSFA on the health and development of infants, indicate the need for enrichment of baby food with DHA and AK. The most studied positive effects of this enrichment are the improvement of visual function and cognitive development of young children. According to new data, increased consumption of LCPSFA is associated with beneficial effects on immune functions and cardiovascular system of infants.